Sound absorbing material
Patent Information
- Application Number
- JP2021011556
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-28
- Filing Date
- 2021-01-27
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-01-27
AI Technical Summary
【0006】 本発明によれば、内部に添加物を含むナノファイバーにより、第1シート及び第2シートの少なくとも一方が形成される。これにより、繊維径を変えることなくナノファイバーの1本1本の重量(密度)及び剛性を変化させることができ、ナノファイバーの吸音特性を変えることができる。つまり、ナノファイバーに添加物を混ぜることで、大きさを変えることなく、吸音率のピーク又は良好に吸音される周波数帯域を低周波側又は高周波側に変更(調整)することができる。本発明によれば、大きさを維持したまま、狙いの周波数帯域(低周波帯域又は高周波帯域)での吸音率を向上させることができる。
Smart Images

Figure 0007641561000001 
Figure 0007641561000002 
Figure 0007641561000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a sound absorbing material. [Background technology]
[0002] Sound-absorbing materials using nanofibers are described, for example, in JP 2017-82346 A and JP 2016-122185 A. These nanofibers are produced by a melt spinning method in which a solid material is melted and extruded from a nozzle to form fibers. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-82346 A [Patent Document 2] JP 2016-122185 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, conventional nanofiber sound absorbing materials have a low sound absorption coefficient in the low frequency band (for example, a band below 2000 Hz), and there is room for improvement. In addition, in order to match the characteristics of the sound absorbing material to the requirements of the installation site, for example, the thickness of the sheet can be changed, but it has been difficult to obtain the targeted sound absorption characteristics (for example, a high sound absorption coefficient in the low frequency band), for example, to adjust the position of the peak sound absorption coefficient. The object of the present invention is to provide a sound absorbing material that can improve the sound absorption coefficient in the targeted frequency band without changing the size. [Means for solving the problem]
[0005] The sound-absorbing material of the present invention comprises a nonwoven fabric, a first sheet arranged on one side of the nonwoven fabric and composed of a first nanofiber, and a second sheet arranged on the other side of the nonwoven fabric and composed of a second nanofiber, wherein at least one of the first nanofiber and the second nanofiber contains an additive therein. Effect of the Invention
[0006] According to the present invention, at least one of the first sheet and the second sheet is formed from nanofibers containing an additive therein. This allows the weight (density) and stiffness of each nanofiber to be changed without changing the fiber diameter, and the sound absorption characteristics of the nanofiber to be changed. In other words, by mixing an additive into the nanofiber, the peak of the sound absorption coefficient or the frequency band in which sound is absorbed well can be changed (adjusted) to the low frequency side or the high frequency side without changing the size. According to the present invention, the sound absorption coefficient in the target frequency band (low frequency band or high frequency band) can be improved while maintaining the size. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a diagram showing the configuration of a sound-absorbing material according to a first embodiment. [Diagram 2] FIG. 11 is a diagram showing the sound absorption coefficient of Example 1 of the first embodiment. [Diagram 3] FIG. 11 is a diagram showing the measurement results of Example 1 of the first embodiment. [Figure 4] FIG. 11 is a diagram showing measurement results of Examples 2 and 3 of the first embodiment and other examples. [Diagram 5] This is an SEM photo (10,000x magnification) of nanofibers mixed with hollow zeolite. [Figure 6] This is an SEM photo (10,000x magnification) of nanofibers mixed with crushed zeolite. [Figure 7] FIG. 11 is a diagram showing measurement results (Thinsulate: calculated value) of Examples 2 and 3 of the first embodiment and other examples. [Figure 8] FIG. 11 is a diagram showing the configuration of a sound-absorbing material according to a second embodiment. [Figure 9]FIG. 13 is a diagram showing measurement results (Thinsulate: calculated value) of Examples 4 and 5 of the second embodiment and other examples. [Figure 10] FIG. 13 is a diagram showing measurement results of Examples 4 and 5 of the second embodiment and other examples. [Figure 11] FIG. 13 is a diagram showing measurement results (Thinsulate: calculated value) of Examples 6 and 7 of the second embodiment and other examples. [Figure 12] FIG. 13 is a diagram showing measurement results of Examples 6 and 7 of the second embodiment and other examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Each drawing used in the description is a conceptual diagram. First Embodiment 1, the sound-absorbing material 1 of the first embodiment includes a nonwoven fabric 2, a first sheet 3, and a second sheet 4. The nonwoven fabric 2 is a known material, and is made of, for example, polypropylene (PP), polyethylene terephthalate (PET), etc. The nonwoven fabric 2 can be said to be the base material of the sound-absorbing material 1.
[0009] The first sheet 3 is disposed on one side 21 (front side) of the nonwoven fabric 2, and is a sheet member made of first nanofibers 31. The second sheet 4 is disposed on the other side 22 (back side) of the nonwoven fabric 2, and is a sheet member made of second nanofibers 41. The nonwoven fabric 2, the first nanofibers 31, and the second nanofibers 41 are integrally bonded, for example, by being entangled or partially bonded together, to form a single nonwoven fabric structure.
[0010] At least one of the first nanofiber 31 and the second nanofiber 41 (hereinafter also referred to as "nanofibers 31, 41") contains an additive 5 therein. The additive 5 can also be called an additive, mass, mixture, or addition. The additive 5 is a substance (material) different from the resin material constituting the nanofibers 31, 41. In other words, the density of the additive 5 is different from the density of the resin material constituting the nanofibers 31, 41. The additive 5 is formed, for example, in a granular shape within the nanofibers 31, 41. It can be said that the nanofibers 31, 41 contain a solid additive 5. A plurality of granular additives 5 are arranged inside and on the surface of the fibrous nanofibers 31, 41. The first nanofiber 31 and the second nanofiber 41 can also be called resin nanofibers containing the additive 5 therein. The first nanofiber 31 and the second nanofiber 41 may contain the same additive 5 therein. At least a portion of the additives 5 has a size (for example, a particle size) smaller than the fiber diameter of the nanofibers 31, 41. The additives 5 may also include one having a particle size (maximum width) larger than the fiber diameter of the nanofibers 31, 41.
[0011] (Manufacturing method) A manufacturing method of the nanofibers 31 and 41 will be briefly described. The nanofibers 31 and 41 are manufactured using an electrospinning method (also called an electrospinning method or a solvent spinning method). The electrospinning method is a known method in which, for example, a raw material solution is filled into a nozzle, a voltage is applied between the nozzle and a site where the nanofibers are deposited and collected (collection site), the raw material solution is drawn out from the nozzle and turned into nanofibers, and the nanofibers are produced on the collection site.
[0012] The method for producing the nanofibers 31 and 41 includes a raw material solution preparation step of preparing a raw material solution, and a nanofiber preparation step of preparing nanofibers by electrospinning using the raw material solution prepared in the raw material solution preparation step. In the raw material solution preparation step, a first solution is prepared by dissolving a polymer material in a solvent. When the polymer material that is the main raw material of the nanofibers is polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyamide, or polyimide, the solvent is preferably, for example, N-N-dimethylformamide (DMF), N-N-dimethylacetamide (DMAc), or N-methylpyrrolidone (NMP).
[0013] Then, in the raw material solution preparation step, a second solution is prepared by mixing the additive 5 with the first solution. A dispersant may be mixed into the second solution. In the nanofiber preparation step, an electrospinning device is used to prepare nanofibers 31, 41 from the raw material solution (second solution) by electrospinning. Then, the nanofibers 31, 41 form the sheets 3, 4. When the nanofibers 31, 41 are to be produced so that they each contain a different additive 5, the above production method may be carried out individually.
[0014] (Effects of the first embodiment) According to the first embodiment, at least one of the first sheet 3 and the second sheet 4 is formed by nanofibers containing the additive 5 therein. This allows the weight (density) and stiffness of each nanofiber to be changed without changing the fiber diameter, and the sound absorption characteristics (e.g., resonance frequency) of the nanofibers to be changed. In other words, the peak of the sound absorption coefficient or the frequency band in which sound is absorbed well can be changed to the low frequency side or the high frequency side without changing the size. According to the present invention, the sound absorption coefficient in the target frequency band (low frequency band or high frequency band) can be improved while maintaining the size. According to the present invention, a sound absorbing material that meets the requirements of the mounting object can be provided without changing the shape of the mounting object (e.g., the shape of the part where the sound absorbing material is arranged). It is difficult to mix the additive 5 into the nanofibers by the melt spinning method, but it is possible by the electrospinning method using a solution containing the additive 5 as in the first embodiment.
[0015] For example, asphalt sheets have been used as low-frequency sound-absorbing materials, but in the first embodiment, the light and thin sound-absorbing material 1 with the above configuration can absorb low-frequency sounds well. Sound absorption in the low-frequency range is required in vehicles such as trains and automobiles. The first embodiment is also advantageous in terms of reducing the weight and size of vehicles or machines.
[0016] Example 1 In Example 1, the first nanofibers 31 and the second nanofibers 41 contain the same additive 5 therein. The additive 5 is zeolite. The first nanofibers 31 and the second nanofibers 41 each have an average fiber diameter of about 200 nm. The nonwoven fabric 2 has a thickness of 5 mm. The first sheet 3 and the second sheet 4 each have a thickness of 100 μm. The raw material of the first nanofibers 31 and the second nanofibers 41 is polyvinylidene fluoride (PVDF). The manufacturing method is the electrospinning method as described above.
[0017] The intrafiber ratios of the nanofibers 31 and 41 formed by the electrospinning method are as follows: Synthetic zeolite adsorbent Zeolum F-9 (Tosoh Corporation): 15.8% PDVF copolymer Solef21216 (Solvay): 84.2% The liquid ratio of the raw material solution (second solution) was 1.5% for the former (zeolite) and 8% for the latter (PVDF).
[0018] The sound absorption coefficient of the sound absorbing material 1 of Example 1 was measured by the A-tube method. The sound absorption coefficient (normal incidence sound absorption coefficient) of sounds with frequencies of 125 Hz to 2000 Hz from a direction perpendicular to the planar direction of the sound absorbing material 1 was measured using a vertical sound absorbing system using an acoustic impedance tube. The measurement results are shown in FIG. 2.
[0019] Fig. 2 shows other results measured by the same measurement method as in Example 1, namely, the sound absorption coefficients of a 13 mm thick commercially available Thinsulate, a 5 mm thick nonwoven fabric (substrate), and a 5.5 mm thick sound absorbing material without zeolite (additive 5). Fig. 3 shows the data in Fig. 2 and other data, namely, a 200 μm thick nanofiber sheet without zeolite (additive 5), a 100 μm thick nanofiber sheet (first sheet 3 or second sheet 4) with zeolite (additive 5), the acrylic plate measurement jig only, and a blank.
[0020] In this experiment, the raw material of the nanofiber is the same PDVF as in Example 1, and the only difference is the presence or absence of zeolite. The nonwoven fabric 2 is also the same as the nonwoven fabric 2 in Example 1. The sound absorbing material without zeolite is composed of the nonwoven fabric 2, a first nanofiber sheet without additive 5 arranged on one side of the nonwoven fabric 2, and a second nanofiber sheet without additive 5 arranged on the other side of the nonwoven fabric 2.
[0021] As shown in Fig. 2, the sound absorbing material 1 of Example 1 has a sound absorption coefficient peak shifted to the lower frequency side compared to a sound absorbing material without zeolite. The sound absorbing material 1 of Example 1 has a sound absorption coefficient peak at frequencies of 1500 Hz or less, and the peak value exceeds 30%. It can be said that the sound absorbing material 1 of Example 1 has a frequency band (frequency region) in which the sound absorption coefficient exceeds 30% in the frequency range of 1000 Hz or more and 1500 Hz or less.
[0022] Furthermore, the sound absorbing material 1 of Example 1 has a significantly improved sound absorption coefficient in a band on the lower frequency side than the peak (for example, a range of 800 Hz to 1250 Hz) compared to the measurement results of the nonwoven fabric 2. In this way, the sound absorbing material 1 of Example 1 can shift the peak of the sound absorption coefficient or the frequency band in which sound is absorbed well to the lower frequency side, and can improve the sound absorption coefficient in the low frequency band.
[0023] (others) The nanofibers 31 and 41 may contain different additives 5. Alternatively, only one of the nanofibers 31 and 41 may contain the additive 5. The sound absorbing material 1 preferably has a peak sound absorption coefficient at a frequency of 2000 Hz or less. The present invention is based on the new knowledge that the sound absorption characteristics change when an additive is added to the nanofiber, and the same effect is expected for additives other than those in the above-mentioned embodiment. It is considered that the sound absorption characteristics change when the weight of the nanofiber (each fiber) changes due to the addition of the additive. According to the present invention, the sound absorption characteristics (e.g., peak position) can be selectively changed by selecting the additive 5. It can also be said that the sound absorption coefficient can be adjusted by the additive 5 according to the present invention. According to the present invention, the sound absorption coefficient in the low frequency band (e.g., 2000 Hz or less) can be increased.
[0024] Example 2 In Example 2, the first nanofiber 31 and the second nanofiber 41 contain the same additive 5 inside. The additive 5 is cerium oxide (CeO2). The first nanofiber 31 and the second nanofiber 41 each have an average fiber diameter of about 200 nm. The nonwoven fabric 2 has a thickness of 5 mm. The first sheet 3 and the second sheet 4 each have a thickness of 100 μm. The raw material of the first nanofiber 31 and the second nanofiber 41 is polyvinylidene fluoride (PVDF). The manufacturing method is the electrospinning method as described above.
[0025] The intrafiber ratios of the nanofibers 31 and 41 formed by the electrospinning method are as follows: Cerium oxide, special grade (Kanto Chemical): 16.59% PDVF copolymer Solef21216 (Solvay): 83.41% The liquid ratio of the raw material solution (second solution) was 1.79% for the former (cerium oxide) and 9.00% for the latter (PVDF).
[0026] The sound absorption coefficient of the sound absorbing material 1 of Example 2 was measured by normal incidence sound absorption coefficient measurement. The sound absorption coefficient (normal incidence sound absorption coefficient) of sounds with frequencies of 125 Hz to 5000 Hz from a direction perpendicular to the planar direction of the sound absorbing material 1 was measured using WinZac (manufactured by Nihon Onkyo Engineering Co., Ltd.). The measurement results are shown by the dashed line in Fig. 4.
[0027] Example 3 In Example 3, the first nanofibers 31 and the second nanofibers 41 contain the same additive 5 inside. The additive 5 is hollow zeolite. The first nanofibers 31 and the second nanofibers 41 each have an average fiber diameter of about 200 nm. The nonwoven fabric 2 has a thickness of 5 mm. The first sheet 3 and the second sheet 4 each have a thickness of 100 μm. The raw material of the first nanofibers 31 and the second nanofibers 41 is polyvinylidene fluoride (PVDF). The manufacturing method is the electrospinning method as described above.
[0028] The hollow zeolite is a zeolite having a different shape from the zeolite of Example 1 (hereinafter referred to as "crushed zeolite"). The hollow zeolite is formed so that each particle is a hollow (not clogged) sphere. On the other hand, the crushed zeolite is, for example, a hollow zeolite that has been crushed and made fine (it can be said to be solid). The density of the hollow zeolite is smaller than the density of the crushed zeolite and the density of the nanofiber (density of crushed zeolite>density of nanofiber>density of hollow zeolite). Based on the nanofiber, the specific gravity of the crushed zeolite and cerium oxide is large, and the specific gravity of the hollow zeolite is small.
[0029] For reference, FIG. 5 shows a nanofiber containing hollow zeolite, and FIG. 6 shows a nanofiber containing crushed zeolite. The average particle size (average width) of cerium oxide and crushed zeolite is smaller than the fiber diameter of the nanofiber. Some hollow zeolites have a maximum width (particle size) larger than the fiber diameter of the nanofiber. Therefore, as shown in FIG. 5, the nanofiber containing hollow zeolite has unevenness formed in the fiber, forming a meandering uneven structure. On the other hand, as shown in FIG. 6, the nanofiber containing crushed zeolite has zeolite uniformly contained in the fiber, and the fiber shape is also uniform. As can be seen from FIG. 5 and FIG. 6, the size of the additive 5 can be said to be a size that can be fixed by one fiber of the nanofiber.
[0030] The intrafiber ratios of the nanofibers 31 and 41 formed by the electrospinning method are as follows: Synthetic zeolite adsorbent Zeolum F-9 (Tosoh Corporation): 16.59% PDVF copolymer Solef21216 (Solvay): 83.41%
[0031] The liquid ratio of the raw material solution (second solution) was 1.79% for the former (hollow zeolite) and 9.00% for the latter (PVDF). The sound absorption coefficient of the sound-absorbing material 1 of Example 3 was measured by the same measurement method as in Example 2. The measurement results are shown by the two-dot chain line in Figure 4.
[0032] In Examples 2 and 3, the first sheet 3 and the nonwoven fabric 2, and the second sheet 4 and the nonwoven fabric 2 are each joined with double-sided tape placed on a part (here, the center position) of the nonwoven fabric 2. The double-sided tape is preferably placed on a part of the nonwoven fabric 2 so that the characteristics of the double-sided tape do not significantly affect the characteristics of the entire sound-absorbing material 1. The double-sided tape is placed on each of the sheets 3 and 4 in a size that allows positioning. If the double-sided tape is placed on the entire surface of the nonwoven fabric 2, the effect of the double-sided tape will be greater.
[0033] Fig. 4 also shows the results of measurements of other sound-absorbing materials measured using the same measurement method as in Examples 2 and 3. That is, Fig. 4 shows a commercially available Thinsulate with a thickness of 13 mm (shown by a dotted line) and a nonwoven fabric with a thickness of 5 mm bonded to both sides with nanofiber sheets not containing additive 5 in Examples 2 and 3 (hereinafter referred to as "first pure nano sound-absorbing material") (shown by a solid line). Hereinafter, the sound-absorbing material 1 of Example 2 will be referred to as the "first cerium oxide-containing sound-absorbing material", and the sound-absorbing material 1 of Example 3 will be referred to as the "first hollow zeolite-containing sound-absorbing material".
[0034] (Examination of Figure 4) FIG. 4 shows the measurement results of multiple sound-absorbing materials manufactured under the same conditions and measured by the same method, with only the additive 5 being different. According to the results, the peak sound absorption coefficient of the first sound-absorbing material containing cerium oxide is shifted to the lower frequency side compared to the first pure nano sound-absorbing material. Also, the peak sound absorption coefficient of the first sound-absorbing material containing hollow zeolite is shifted to the higher frequency side compared to the first pure nano sound-absorbing material. In this way, by changing the additive 5, it was possible to change the sound absorption characteristics (the frequency at which the sound absorption coefficient reaches its peak) without changing the fiber diameter of the nanofiber.
[0035] The peak in the study of FIG. 4 is the apex (also called the maximum value) of a curve drawn upwards with frequency on the horizontal axis, and is also the point where the difference with a predetermined reference value is the largest (maximum value > predetermined reference value). The predetermined reference value is the sound absorption coefficient of Thinsulate (commercially available product) of the same thickness as the sound absorbing material 1 at the same frequency as the maximum value being compared (see the dotted line in FIG. 7). Note that the sound absorption coefficient of Thinsulate in FIG. 7 is a calculated value converted from the sound absorption coefficient (measured value) of Thinsulate with a thickness of 13 mm to the sound absorption coefficient of Thinsulate with a thickness of 5.2 mm. Note that the peak in the study of FIG. 4 can also be said to be the point where the maximum value and maximum value are reached at a frequency of 5000 Hz or less.
[0036] <Second embodiment> As shown in FIG. 8, the sound-absorbing material 10 of the second embodiment includes a sheet 6 made of nanofibers 61, a first nonwoven fabric 7 arranged on one side 6a of the sheet 6, and a second nonwoven fabric 8 arranged on the other side 6b of the sheet 6. The nanofibers 61 contain an additive 5 inside. The nonwoven fabrics 7 and 8 are formed in a sheet shape. As in Examples 2 and 3, the sheet 6 and the first nonwoven fabric 7, and the sheet 6 and the second nonwoven fabric 8 are partially joined (to the extent that they can be positioned) with double-sided tape. The nanofibers 61 and the sheet 6 are manufactured in the same manner as in the first embodiment. Even with this configuration, the sound-absorbing characteristics can be changed by the additive 5 while maintaining the size of the sound-absorbing material, based on the same principle as in the first embodiment.
[0037] Example 4 In Example 4, the additive 5 is cerium oxide. The average fiber diameter of the nanofibers 61 is about 200 nm. The first nonwoven fabric 7 and the second nonwoven fabric 8 each have a thickness of 5 mm. The sheet 6 has a thickness of 100 μm. In other words, the sound-absorbing material 10 has a thickness of 10.1 mm. The raw material of the nanofibers 61 is polyvinylidene fluoride (PVDF). The manufacturing method is the electrospinning method as described above.
[0038] The intrafiber ratio of the nanofibers 61 formed by the electrospinning method is as follows. Cerium oxide, special grade (Kanto Chemical): 16.59% PDVF copolymer Solef21216 (Solvay): 83.41% The liquid ratio of the raw material solution (second solution) was 1.79% for the former (cerium oxide) and 9.00% for the latter (PVDF).
[0039] The sound absorption coefficient of the sound-absorbing material 10 of Example 4 was measured by normal incidence sound absorption coefficient measurement. The sound absorption coefficient (normal incidence sound absorption coefficient) of sounds with frequencies of 125 Hz to 5000 Hz from a direction perpendicular to the planar direction of the sound-absorbing material 1 was measured using WinZac (manufactured by Nihon Onkyo Engineering Co., Ltd.). The measurement results are shown by the dashed line in FIG. 9.
[0040] Example 5 In Example 5, the additive 5 is hollow zeolite. The average fiber diameter of the nanofibers 61 is about 200 nm. The first nonwoven fabric 7 and the second nonwoven fabric 8 each have a thickness of 5 mm. The sheet 6 has a thickness of 100 μm. In other words, the sound-absorbing material 10 has a thickness of 10.1 mm. The raw material of the nanofibers 61 is polyvinylidene fluoride (PVDF). The manufacturing method is the electrospinning method as described above.
[0041] The intrafiber ratio of the nanofibers 61 formed by the electrospinning method is as follows. Synthetic zeolite adsorbent Zeolum F-9 (Tosoh Corporation): 16.59% PDVF copolymer Solef21216 (Solvay): 83.41%
[0042] The liquid ratio of the raw material solution (second solution) was 1.79% for the former (hollow zeolite) and 9.00% for the latter (PVDF). The sound absorption coefficient of the sound-absorbing material 10 of Example 5 was measured by the same measuring method as in Example 4. The measurement results are shown by the two-dot chain line in FIG. 9.
[0043] Fig. 9 also shows the measurement results of other sound-absorbing materials measured by the same measurement method as in Examples 4 and 5. That is, Fig. 9 shows a commercially available Thinsulate with a thickness of 10.1 mm (calculated value: shown by a dotted line) and a nanofiber sheet (100 µm) not containing additive 5 in Examples 4 and 5 in which a nonwoven fabric with a thickness of 5 mm is bonded to both sides (hereinafter referred to as the "second pure nano sound-absorbing material") (shown by a solid line). Hereinafter, the sound-absorbing material 10 of Example 4 will be referred to as the "second cerium oxide-containing sound-absorbing material", and the sound-absorbing material 10 of Example 5 will be referred to as the "second hollow zeolite-containing sound-absorbing material".
[0044] (Study of Figure 9) 9 shows the measurement results of a number of sound-absorbing materials manufactured under the same conditions and measured by the same method, with only the additive 5 being different. According to the results, the peak sound absorption coefficient of the second cerium oxide-containing sound-absorbing material is shifted to the lower frequency side compared to the second pure nano sound-absorbing material. Also, the peak sound absorption coefficient of the second hollow zeolite-containing sound-absorbing material is shifted to the higher frequency side compared to the second pure nano sound-absorbing material. As in the first embodiment, by changing the additive 5, it was possible to change the sound absorption characteristics (the frequency at which the sound absorption coefficient reaches its peak) without changing the fiber diameter of the nanofiber.
[0045] The peak in the study of FIG. 9, as in the study of FIG. 4, is the apex (also called the maximum value) of a curve drawn upwards with the horizontal axis being frequency, and is also the point where the difference with the predetermined reference value is the largest (maximum value>predetermined reference value). The predetermined reference value is the sound absorption coefficient of Thinsulate (commercial product) of the same thickness as the sound absorbing material 10 at the same frequency as the maximum value to be compared (see the dotted line in FIG. 9). Note that the sound absorption coefficient of Thinsulate in FIG. 9 is a calculated value converted from the sound absorption coefficient (measured value) of Thinsulate with a thickness of 13 mm to the sound absorption coefficient of Thinsulate with a thickness of 10.1 mm by calculation. For reference, a graph showing the sound absorption coefficient of Thinsulate with a thickness of 13 mm is shown in FIG. 10. Also, the peak in the study of FIG. 9 can be said to be the point where the maximum value is reached at a frequency of 1000 Hz or less.
[0046] Example 6 The sound absorbing material 10 of Example 6 is formed by using the same sheet 6 (containing cerium oxide) as the sheet 6 of Example 4, and using Thinsulate of the same thickness instead of the first nonwoven fabric 7 and the second nonwoven fabric 8. That is, the sheet 6 is formed of nanofibers 61 having a thickness of 100 μm and containing cerium oxide as the additive 5. Thinsulate (thickness 6.5 mm) as the first nonwoven fabric 7 is attached to one side of the sheet 6, and Thinsulate (thickness 6.5 mm) as the second nonwoven fabric 8 is attached to the other side of the sheet 6. The thickness of the sound absorbing material 10 of Example 6 is 13.1 mm. The sound absorption coefficient of the sound absorbing material 10 of Example 6 was measured by the same measurement method as in Example 4. The measurement result is shown by the dashed line in FIG. 11.
[0047] Example 7 The sound-absorbing material 10 of Example 7 is obtained by changing the sheet 6 of Example 6 to the same one as the sheet 6 (containing hollow zeolite) of Example 5. That is, the sheet 6 of Example 7 is 100 μm thick and is formed of nanofibers 61 with hollow zeolite as additive 5. Thinsulate (thickness 6.5 mm) as the first nonwoven fabric 7 is attached to one side of the sheet 6, and Thinsulate (thickness 6.5 mm) as the second nonwoven fabric 8 is attached to the other side of the sheet 6. The sound-absorbing material 10 of Example 7 has a thickness of 13.1 mm. The sound absorption coefficient of the sound-absorbing material 10 of Example 7 was measured by the same measurement method as in Example 4. The measurement results are shown by the two-dot chain line in FIG. 11.
[0048] Fig. 11 also shows the measurement results of other sound-absorbing materials measured by the same measurement method as in Examples 6 and 7. That is, Fig. 11 shows commercially available Thinsulate with a thickness of 13.1 mm (calculated value: shown by dotted line) and a nanofiber sheet (100 µm) not containing additive 5 in Examples 6 and 7 in which Thinsulate with a thickness of 6.5 mm is bonded to both sides (hereinafter referred to as "third pure nano sound-absorbing material") (shown by solid line). Hereinafter, the sound-absorbing material 10 of Example 6 will be referred to as the "third cerium oxide-containing sound-absorbing material", and the sound-absorbing material 10 of Example 7 will be referred to as the "third hollow zeolite-containing sound-absorbing material".
[0049] (Consider Figure 11) 11 shows the measurement results of a number of sound-absorbing materials manufactured under the same conditions and measured by the same method, with only the additive 5 being different. According to the results, the sound absorption coefficient peak of the third sound-absorbing material containing cerium oxide is shifted to the lower frequency side compared to the third pure nano sound-absorbing material. Also, the sound absorption coefficient peak of the third sound-absorbing material containing hollow zeolite is shifted to the higher frequency side compared to the third pure nano sound-absorbing material. As in the first embodiment, by changing the additive 5, it was possible to change the sound absorption characteristics (the frequency at which the sound absorption coefficient reaches its peak) without changing the fiber diameter of the nanofiber.
[0050] The peak in the study of FIG. 11, as in the studies of FIG. 4 and FIG. 9, is the apex (also called the maximum value) of a curve drawn upwards with the horizontal axis being frequency, and is also the point where the difference with the predetermined reference value is the largest (maximum value>predetermined reference value). The predetermined reference value is the sound absorption coefficient of Thinsulate (commercial product) of the same thickness as the sound absorbing material 10 at the same frequency as the maximum value to be compared (see the dotted line in FIG. 11). Note that the sound absorption coefficient of Thinsulate in FIG. 11 is a calculated value converted from the sound absorption coefficient (measured value) of Thinsulate with a thickness of 13 mm to the sound absorption coefficient of Thinsulate with a thickness of 13.1 mm by calculation. For reference, a graph showing the sound absorption coefficient of Thinsulate with a thickness of 13 mm is shown in FIG. 12. Note that the peak in the study of FIG. 11 can also be said to be the point where the maximum value is reached at a frequency of 3000 Hz or less.
[0051] Zeolite and cerium oxide can be regarded as nanoparticles that can be contained within the nanofiber fibers. The nanofibers of this embodiment can be regarded as containing, as additive 5, nanoparticles having a density different from that of the resin material constituting the nanofiber. The nonwoven fabric is a sheet-like material in which fibers are entangled. In this specification, Thinsulate is included in the nonwoven fabric.
[0052] (summary) As in the first and second embodiments, according to the present invention, the sound absorption characteristics can be changed by including the additive 5 in the nanofiber, and sound can be absorbed at a specific frequency. It is considered that mixing the additive 5 having a higher density than the nanofiber into the nanofiber can shift the peak of the sound absorption coefficient to the lower frequency side, and mixing the additive 5 having a lower density than the nanofiber into the nanofiber can shift the peak of the sound absorption coefficient to the higher frequency side. This is considered to be the result of the density, stiffness, etc. of the sheets 3, 4, and 6 manufactured by mixing the additive 5 into the nanofiber changing, which affects the sound absorption characteristics.
[0053] Furthermore, according to the present invention, the sound absorption characteristics of the sheets 3, 4, and 6 can be changed without changing the fiber diameter of the nanofibers 31, 41, and 61. Therefore, only the sound absorption characteristics can be changed without changing the thickness of the sound absorbing material 1, 10. For example, it is considered that increasing the fiber diameter of the nanofibers makes it easier to absorb low-frequency sounds, but if the thickness of the sheet is maintained, the surface area that reflects the sound is reduced, which may affect the absorption rate. In other words, it is considered that in order to improve the sound absorption rate of low frequencies, the fiber diameter of the nanofibers must be increased and the thickness of the sheet must also be increased.
[0054] However, according to the present invention, since the sound absorption characteristics can be changed without changing the thickness of the sheet, for example, it is possible to increase the low-frequency sound absorption rate without increasing the size of the sound absorbing material. According to the present invention, it is also not necessary to change the shape of the housing part of the sound absorbing material in the installation destination (for example, a vehicle, etc.). Conventionally, it has been difficult to improve the sound absorption rate in the low-frequency band, especially with a light material. However, according to the present invention, it is possible to improve the sound absorption rate in the low-frequency band by mixing a specific additive 5 (for example, zeolite or cerium oxide, which has a higher density than nanofibers) with nanofibers. Furthermore, the sound-absorbing material of the present invention may have any configuration as long as it includes a sheet 6 made of nanofibers 61 containing an additive 5, and a nonwoven fabric 7 arranged on one side 6a of the sheet 6. Even with this configuration, the frequency band with good sound absorption coefficient can be adjusted by the additive 5. For example, when a sound-absorbing material with symmetrical front and back is required, in this configuration, a nonwoven fabric 8 may be added to the other side 6b of the sheet 6, or a sheet 6 may be added to the other side of the nonwoven fabric 7. [Explanation of symbols]
[0055] 1, 10...sound-absorbing material, 2...nonwoven fabric, 21...one side, 22...other side, 3...first sheet, 31...first nanofiber, 4...second sheet, 41...second nanofiber, 5...additive, 6...sheet, 61...nanofiber, 6a...one side, 6b...other side, 7...first nonwoven fabric, 8...second nonwoven fabric.
Claims
1. Nonwoven fabric, a first sheet disposed on one surface of the nonwoven fabric and made of first nanofibers; a second sheet disposed on the other surface of the nonwoven fabric and made of second nanofibers; Equipped with At least one of the first nanofiber and the second nanofiber contains an additive therein; the density of the additive is less than the densities of the first nanofibers and the second nanofibers; In the sound absorption coefficient of a sound having a frequency of 125 Hz to 5000 Hz, the peak of the sound absorption coefficient is shifted to the high frequency side compared to a case in which the first nanofiber and the second nanofiber do not contain the additive. Sound absorbing material.
2. A sheet made of nanofibers; A first nonwoven fabric disposed on one surface of the sheet; Equipped with The nanofibers include an additive therein, The density of the additive is less than the density of the nanofibers; In the sound absorption coefficient of sounds having frequencies of 125 Hz to 5000 Hz, the peak of the sound absorption coefficient is shifted to the higher frequency side compared to when the nanofiber does not contain the additive. Sound absorbing material.
3. A second nonwoven fabric is disposed on the other surface of the sheet. The sound absorbing material according to claim 2. Sound absorbing material.
4. Nonwoven fabric, a first sheet disposed on one surface of the nonwoven fabric and made of first nanofibers; a second sheet disposed on the other surface of the nonwoven fabric and made of second nanofibers; Equipped with At least one of the first nanofiber and the second nanofiber contains an additive therein; The sound absorption coefficient has a peak at a frequency of 2000 Hz or less, The density of the additive is greater than the density of the first nanofibers and the second nanofibers; Sound absorbing material.
5. Nonwoven fabric, a first sheet disposed on one surface of the nonwoven fabric and made of first nanofibers; a second sheet disposed on the other surface of the nonwoven fabric and made of second nanofibers; Equipped with At least one of the first nanofiber and the second nanofiber contains an additive therein; The sound absorption coefficient has a peak at a frequency of 2000 Hz or less, The additive is cerium oxide. Sound absorbing material.
6. Nonwoven fabric, a first sheet disposed on one surface of the nonwoven fabric and made of first nanofibers; a second sheet disposed on the other surface of the nonwoven fabric and made of second nanofibers; Equipped with At least one of the first nanofiber and the second nanofiber contains an additive therein; The sound absorption coefficient has a peak at a frequency of 2000 Hz or less, The additive is a zeolite. Sound absorbing material.
7. The first nanofiber and the second nanofiber contain the same additive therein.
7. The sound absorbing material according to claim 1, 4, 5 or 6.
8. The sound-absorbing material according to any one of claims 1 to 3, wherein the additive is zeolite.
9. Nonwoven fabric, a first sheet disposed on one surface of the nonwoven fabric and made of first nanofibers; a second sheet disposed on the other surface of the nonwoven fabric and made of second nanofibers; Equipped with The first nanofiber and the second nanofiber contain the same additive therein, The density of the additive is 0.42 g / cm 3 1.78g / cm or more 3 is less than The peak of the sound absorption coefficient is shifted to the high frequency side compared to when the first nanofiber and the second nanofiber do not contain the additive. Sound absorbing material.
10. A sheet made of nanofibers; A first nonwoven fabric disposed on one surface of the sheet; A second nonwoven fabric disposed on the other surface of the sheet; Equipped with The nanofibers include an additive therein, The density of the additive is 0.42 g / cm 3 1.78g / cm or more 3 is less than The peak of the sound absorption coefficient is shifted to the high frequency side compared to when the nanofiber does not contain the additive. Sound absorbing material.
Citation Information
Patent Citations
Sound absorbing material and method of manufacturing the same
JP2016113767A
Sound absorber
JP2016122185A
Nonwoven nanofiber fabric and sound absorption material made therefrom
JP2017082346A
Laminate sound absorber containing ultra-fine fiber
JP2018199253A
Laminate sound absorber
JP2019155640A